Factors Influence On Privacy Issues In The E- Banking Websites - A Study With Reference To Commercial Banks In Theni District - K.MATHANKUMAR; Dr. S.BALAMURUGAN (Elementary Education Online, 2023)
This paper gives a brief analysis of the factor influence on privacy issues in the e-banking websites in commercial banks at Theni District. This study is an empirical research. The primary data were collected by personal interview of the selected respondents by using interview schedule. The primary data were collected from the bank customers directly during the month of August 2020 to January 2021. The researcher used convenient sampling method to collect data from the sample respondents. First hand data were collected from the respondents directly by the researcher himself with the help of an interview schedule. Percentage analysis and rotated matrix were used to analyse the data. This paper reveals that out of twenty six variables the Six factors were extracted namely “Familiarity of cyber crimes”, “Trust”, “Perceived risk”, “Security Concern”. All the attributes are formed under each factor had high associations. High value of KaisarMeyer-Olikin measure of sampling adequacy (0.776) indicates the correlation between the pairs at variables explained by other variables and thus factor analysis was considered to be appropriate in this model. Cronbach’s Alpha is more than 0.64 in all factors. The researcher interested to find out what are the factors influence the privacy issues in the E-banking websites of commercial banks in Theni district. Finally conclusions were drawn and suggestions were offered.